1985
DOI: 10.3109/00016358509046506
|View full text |Cite
|
Sign up to set email alerts
|

The effect of new complete dentures on mastication and dietary intake

Abstract: Masticatory efficiency, the subjective experience of masticatory performance, and dietary intake were measured for 43 subjects who were provided with new complete dentures. The subjects were tested on three occasions: with the old complete dentures, with the new complete dentures when free from symptoms, and with the new dentures about 4 months after insertion. Masticatory efficiency and the subjective experience of masticatory performance increased significantly when the subjects were provided with new dentur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1
2

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 21 publications
4
56
1
2
Order By: Relevance
“…3 and 4 show that the CD-group still had prob lems with chewing tough and hard food. These results correspond with those of G u n n e & W a l l (34). They reported that new conventional complete dentures im proved the subjective chewing ability, but that chewing tough or hard foodstuffs was difficult.…”
Section: %supporting
confidence: 79%
“…3 and 4 show that the CD-group still had prob lems with chewing tough and hard food. These results correspond with those of G u n n e & W a l l (34). They reported that new conventional complete dentures im proved the subjective chewing ability, but that chewing tough or hard foodstuffs was difficult.…”
Section: %supporting
confidence: 79%
“…Die antagonistichewing rates are the main criteria for defining impaired masticatory function [102,103], the parameter for masticatory performance is usually defined by the size distribution of food particles after a given number of masticatory cycles [4]. The screening technique already used in the 1920s is still in use today [26,28]. Alternatively, masticatory efficiency is described by the number of masticatory cycles necessary to break up food to a specific maximum particle size [72].…”
Section: Der Kauprozessmentioning
confidence: 99%
“…Optimizing full dentures has been shown to improve chewing efficiency (Gunne & Wall, 1985). In the study of Heath (1972), persons with better fitting dentures were able to chew twice as many hard foods as persons with poor fitting dentures.…”
Section: T H E B E N E F I T S O F D E N T a L Prostheses O N C H E Wmentioning
confidence: 99%